The Paradox in Derrida’s Notion Of Forgiveness - Chirawibulrat, Piroon (Journal of the Philosophy and Religion Society of Thailand, 2024)
Jacques Derrida proposes a paradoxical notion within the philosophy of forgiveness, suggesting that forgiveness forgive only the unforgivable. This notion expands the horizons of understanding the ethics of forgiveness while simultaneously making it challenging to implement Derrida’s notion of forgiveness in politic contexts. This article aims to elucidate the paradox in Derrida’s notion of forgiveness and offer critiques to highlight the difficulties in applying Derrida’s forgiveness for the reconciliation of societal conflicts.